Characterization and comparison of bioactive polysaccharides from the tubers of Gymnadenia conopsea. (January 2015) - Lin, Peng-Cheng; Wu, Ding-Tao; Xie, Jing; Zhao, Jing; Li, Shao-Ping
Abstract: Water soluble polysaccharides from seven batches of Gymnadenia conopsea were firstly investigated and compared using high performance size exclusion chromatography coupled with multi-angle laser light scattering/refractive index detector (HPSEC-MALLS/RID) and saccharide mapping based on polysaccharide analysis by carbohydrate gel electrophoresis (PACE), respectively. The results showed that the weight-average molecular weight ( M w ) and the radius of gyration (< S 2 >z 1/2 ) of polysaccharides were ranging from 4.46 × 10 5 to 7.41 × 10 5 Da and 73.3–94.2 nm, respectively. By applying the polymer solution theory, the exponent ( ν ) values of < S 2 >z 1/2 = k M w ν were ranging from 0.36 to 0.42, which indicated that polysaccharides from G. conopsea existed as globular in the aqueous solution. Furthermore, the results showed that α-1, 4- and β-1, 3(4)-glucosidic, α-1, 5-arabinosidic, β-1, 4-mannosidic and α-1, 4-D-galactosiduronic linkages existed in polysaccharides from G. conopsea . The similarity of the hydrolysates of polysaccharides in G. conopsea collected from different regions was high. Moreover, the nitric oxide released from RAW 264.7 cells induced by polysaccharides were significantly affected by their α-1, 5-arabinosidic and β-1, 3(4)-glucosidic, especially α-1, 4-D-galactosiduronic and β-1, 4-mannosidic linkages. These results are beneficial for better understanding of the structures–bioactivity relationship of polysaccharides from G. conopsea, and helpful to improve their pharmacological activity-based quality control. Graphical abstract: Highlights: Physico-chemical characterization of polysaccharides from Gymnadenia conopsea . HPSEC-MALLS/RID and saccharides mapping based on PACE were performed. The chain conformations were firstly provided. Correlation of the chemical structures to the bioactivity of polysacchardes.